Industrial Marketing:Text and Cases - Jasrotia, Namrata Vasudeo (Indian Journal of Marketing, 2016)
The present book review analyzed Francis Cherunilam’s book : Industrial Marketing : Text and Cases. In this book, the author has made an attempt to highlight the concept and basics of industrial marketing. He has also tried to explain the concept of B2B marketing with case studies and relevant examples from the industry. The book is very lucid and easy to understand for beginners. It is very enriched with examples and case studies, which gives the students an easy and comfortable understanding of the topic.